A STUDY ON THE PREVALENCE OF ADVERSE EFFECTS ASSOCIATED WITH SODIUM-GLUCOSE COTRANSPORTER 2 INHIBITOR DAPAGLIFLOZIN IN A TERTIARY CARE CENTRE - ASWINI S; BABU EZHUMALAI; HANUSHA V; SETHUMEENA S (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of this study was to assess the prevalence of adverse effects associated with sodium-glucose cotransporter 2 inhibitors (SGLT2i) dapagliflozin in a real-world setting. Methods: This observational study was conducted prospectively over 3 months in a tertiary care center in India. It focused on in-patients aged over 18 who were diagnosed with heart failure, Type 2 diabetes mellitus, or chronic kidney disease, and undergoing treatment with SGLT2i, specifically dapagliflozin, at doses of 5 or 10 mg. Patients with a glomerular filtration rate of <25 mL/min/1.73 m², pregnant or lactating women, and individuals with end-stage renal disease or undergoing dialysis were excluded from this study. Patient demographics, clinical history, and medication usage were collected using a structured pro forma. Results: Among 60 patients, 15 (25%) experienced adverse effects. Women and those over 50 years had a significantly higher prevalence of adverse effects. The common adverse effects were urinary tract infection 5 (8.3%), urinary-like symptoms 4 (6.6%), gastrointestinal upset 3 (5%), weakness 2 (3%), and hyponatremia 1 (1.6%). The dosage (5 mg and 10 mg) was significantly associated with side effects (p<0.002). Management strategies varied, including discontinuation, temporary halting, or no change in treatment. Conclusion: The observed higher prevalence of adverse effects in older individuals, particularly women, and with higher drug doses further emphasizes the necessity for close clinical monitoring during the initial phases of treatment.